GLOBALIZATION AND IDENTITY: INTERRELATION OF GLOBAL AND LOCAL - Khashiyeva L.V. (Pressing Problems of Public Administration, 2015)
The article is devoted to the study of globalization impact on the national and cultural identity development. The quest for alternative strategies of cultural politics as a mechanism of the reduction of the ethno-cultural identity loss risks in the modern socio-cultural transformation context is initiated. New identification models based on local cultures development that act as forms of resistance to the globalizing pressure on the socio-cultural realm are analyzed.